Case Report: An Unusual First Manifestation of a Pheochromocytoma - Zhai, Qiangrong; Tian, Ci; Deng, Zhengzhao; Liu, Congrong; Ma, Qingbian (Frontiers in Endocrinology, 2021)
We present a 30-year old male presented with hemoptysis as a first manifestation and pulmonary CT scan characteristic of diffuse alveolar hemorrhage. Further abdominal examination discovered a left adrenal mass. Elevated catecholamine and metanephrine levels and subsequent adrenalectomy confirmed the diagnosis of pheochromocytoma. Symptoms of pheochromocytoma are highly variable, which could potentially delay the diagnosis. With careful investigation, emergency medicine practitioners need to be aware of the cunning and changeful manifestations in pheochromocytoma.